Les ateliers de céramique de la Byzacène du Sud-Ouest, nouvelles découvertes - NASR, MONGI (Rei Cretariae Romanae Fautorum Acta, 2024)
Our recent investigations in the Southwest of Byzacena have allowed us to uncover two new production centers: Ain er-Rchiha and Sidi Abdelkader. They have also given us the opportunity to advance irrefutable archaeological evidence of a production of African Red Slip Ware at Henchir en-Nadhour (Majoura). The latter reveals a major discovery: this workshop is the one and only center hitherto identified producing the C/E and E categories that have remained, until now, geographically unlocated. Moreover, these discoveries have revealed, in addition to the trading areas, a true spatial and categorical distribution of ceramic workshops in this region.